ON SOME OUTPUT PROCESSES IN THE SYSTEMS \(M/G/1\) AND \(M^X/G/1\) - Georgieva, Magdalena (Matematichki Bilten, 1993)
In this paper we discuss the output process of the group of unserviced customers generated during the waiting time in the systems \(M/G/1\) and \(M^X/G/1\). For some special distributions of the servicing time we have found the distributions of the moments for the batches of customers when they leave the systems, as well as the distributions of the size of the batches in explicit form.